From Detection to Response: Thrips parvispinus and the Challenge of Invasive Pest Management in Bangladesh - Mohammad Shaef Ullah; Mohammad Swokat Osman Mojumder; Sabbir Ahamed; Dilruba Sharmin; Md. Saleh Ahmed; Malvika Chaudhary; Ivan Rwomushana (Plant Health Cases, 2026)
Abstract Thrips parvispinus (Karny) (Thysanoptera: Thripidae) is an emerging invasive pest that has expanded its geographical range across multiple continents. This case study draws on a systematic field survey conducted in major vegetable- and fruit-growing regions of Bangladesh between November 2024 and July 2025, encompassing 334 samples across 16 districts. The pest was confirmed morphologically on a wide range of host plants, with chili ( Capsicum annuum ), eggplant (aubergine) ( Solanum melongena ), and papaya ( Carica papaya ) identified as the most severely affected crops. Infestation levels in chili fields reached up to 10 thrips per flower in heavily infested areas, and farmers reported perceived yield losses in chili ranging from 30 to 70%, depending on infestation severity and crop growth stages. Damage symptoms included leaf curling, necrotic streaks, flower abortion, and fruit malformation. Jessore district recorded the highest infestation rate at 79.9% of samples examined, followed by Bogura at 72%. Conventional insecticide applications, with some fields receiving up to 6–8 sprays per cropping cycle, proved largely ineffective and raised concerns over pesticide resistance and harm to beneficial insects. IPM strategies – including cultural practices, biological control, and phytosanitary measures – are essential responses to the pest’s establishment and spread towards new areas. The case illustrates the challenges of managing a rapidly invasive, polyphagous pest and the risks of over-reliance on synthetic pesticides. Information © The Authors 2026